(untitled) (Journal of the College of Basic Education, 2022)
Ukraine’s sensitive location between Russia and the members of NATO, being the largest separating country between them, as well as its occupation of more than half of the area of ​​​​the eastern gate to Europe, and this gate is the main reason for the crossing of threats throughout history, when the Ukraine crisis is placed in the broad and permanent strategic context and its impact, therefore, on its future Geopolitical, we will find that the conflict between Russia on the one hand and NATO on the other hand will take another turn and will affect the geopolitical future of Ukraine.